Chapter L'immagine di Magellano nei primi racconti della circumnavigazione del globo - Perocco, Daria (Studi e saggi, 2021)
The journey of the Portuguese Magellan, one of the greatest adventures attempted by a man in the sixteenth century, had an inauspicious end for its deviser (Magellan died in Mactan on April 27, 1522). But even more inauspicious was the narration of his adventure because the only ship of the initial expedition, which returned home, was led by a Spaniard against him. The text retraces the first testimonies of the voyage, especially taking into consideration the press of the navigations and voyages that that adventure spread throughout the world.